2022
DOI: 10.1002/cb.2077
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of conflicting reviews on customers' purchase intentions from a product attributes perspective

Abstract: Numerous studies have investigated the effects of conflicting online reviews on purchase intention. However, only a few studies have focused on the effects from a product attributes perspective. The present study seeks to investigate the role of conflicting online reviews between two different attributes in online consumption scenario that can bridge this gap. Across two experiments, the findings revealed that compared with a medium evaluation, conflicting extreme evaluation reviews between two different attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Our findings on consumers' challenges with accents when engaging with AIIVAs offer significant theoretical contributions to consumer behaviour and human‐computer interaction. Our study identifies the behaviours of consumers when they engage with their accent, which is often a challenge for AIIVAs beyond the language they have been trained to respond to, a product attribute that can influence consumer engagement (Xu & Jin, 2022). Although some findings of the study are in sync with previous research on AIIVAs (Acikgoz & Vega, 2021; Gulshan & Dhage, 2019; Moussalli & Cardoso, 2020; Tyutelova et al, 2020), our study is the first of its kind exploring accents in the field of research on AIIVAs.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on consumers' challenges with accents when engaging with AIIVAs offer significant theoretical contributions to consumer behaviour and human‐computer interaction. Our study identifies the behaviours of consumers when they engage with their accent, which is often a challenge for AIIVAs beyond the language they have been trained to respond to, a product attribute that can influence consumer engagement (Xu & Jin, 2022). Although some findings of the study are in sync with previous research on AIIVAs (Acikgoz & Vega, 2021; Gulshan & Dhage, 2019; Moussalli & Cardoso, 2020; Tyutelova et al, 2020), our study is the first of its kind exploring accents in the field of research on AIIVAs.…”
Section: Discussionmentioning
confidence: 99%
“…First, we delineated the relationship between no feedback and purchase intention with perceived risk. Previous research has shown that various factors such as personality, information, price, and others all affect purchase intention (Bell & Arthur Jr., 2008; Chang & Wildt, 1994; Chatterjee, 2001; Xu & Jin, 2022), and several studies have examined reputation and feedback in online markets (Filieri, Lin, et al, 2021; Filieri, Raguseo, & Vitari, 2021; Lee et al, 2008; Shen & Liu, 2018a, Shen & Liu, 2018b). Most of the existing research has focused on the relationships between positive or negative reviews and purchase intention (Filieri et al, 2022; Lee et al, 2008; Park et al, 2007; Park & Kim, 2008), and there has been little research investigating transactions with no feedback.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…With the emergence of Web 3.0, online reviews have become an essential outlet for consumer communication (Chanias et al, 2019;Wang et al, 2018a, b;Xu & Jin, 2022). The improvement in customer engagement has been intertwined with the rise of unscrupulous organisations who create spam profiles to promote or denigrate products on social media (Aswani et al, 2018, Aswani et al, 2019, Michail et al, 2022.…”
Section: Proposed Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Consumer reviews are so ubiquitous in the modern world that consumers' purchase intentions and decisions are deeply affected by them (Kwon et al, 2014;Senecal & Nantel, 2004). Purchase intention has been defined as the probability of a consumer's willingness to exhibit a purchase behavior (Nikbin et al, 2022;Wien & Olsen, 2012;Xu & Jin, 2022). It is a well-known measure to predict purchase behavior in the marketing literature One of the major advantages of online reviews is that consumers across various geographical locations can share their buying and product experiences (Chanias et al, 2019).…”
Section: Proposed Research Model and Hypotheses Developmentmentioning
confidence: 99%